The Haggadah of the Kaifeng Jews of China - Wong, Fook-Kong. (The Brill Reference Library of Judaism, 2011)
This comprehensive, textual treatment of the Kaifeng Passover Rite is a significant contribution to the ongoing discussion of the community's origins in particular and to comparative Jewish liturgy in general. The book includes a facsimile of one manuscript and a sample of the other, the full text of the Hebrew/Aramaic and Judeo-Persian Haggadah in Hebrew characters, as well as an English translation. Following a review of the community's history, sources for study, and related scholarly work conducted to date, the languages used in the Haggadah and their backgrounds are discussed in detail. Analysis of the order of the service allows for comparison of the Kaifeng Jewish community's recitation of the Passover liturgy, performance of ritual, and consumption of ceremonial food to other communities in the Jewish Diaspora. The various parts and chapters of the book, including its extensive and meticulous annotations and bibliographical references, provide much fresh and useful material for scholars and readers interested in pre-modern Jewish, Judeo-Persian and Chinese literary traditions and cultures. David Yeroushalmi, Tel Aviv University, 2015